2018
DOI: 10.1002/ijc.31402
|View full text |Cite
|
Sign up to set email alerts
|

Soluble γc receptor attenuates anti‐tumor responses of CD8+ T cells in T cell immunotherapy

Abstract: Previous studies have shown that soluble common γ-chain (sγc) modulates CD4 T cell immunity with antagonistic functions in γc cytokine signaling. However, the role of sγc in functional properties of effector CD8 T cells has not been fully defined. In this study, we report a new mechanism by which the anti-tumor activity of mouse CD8 T cells is suppressed in sγc of their own producing. While sγc significantly inhibits cytotoxicity of CD8 T cells, blocking sγc production by genetic modification leads to potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 44 publications
(78 reference statements)
1
11
0
Order By: Relevance
“…Although there may be concerns about side effects caused by blocking all γc cytokine signaling, we would like to point out that sγc suppresses but not completely abolishes cytokine signaling, unlike a neutralizing antibody. This is in line with our observation that T-cell numbers are reduced but not completely rescued in sγc 7Tg mice to those of WT mice ( Figure 2 b), and IL-2 and IL-15 signaling is reduced but not absent in the presence of sγc [ 13 , 14 , 16 ]. Moreover, we propose that the modification of sγc to a multimer, which may improve affinity to γc cytokine receptors, would induce a more significant antitumor effect.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Although there may be concerns about side effects caused by blocking all γc cytokine signaling, we would like to point out that sγc suppresses but not completely abolishes cytokine signaling, unlike a neutralizing antibody. This is in line with our observation that T-cell numbers are reduced but not completely rescued in sγc 7Tg mice to those of WT mice ( Figure 2 b), and IL-2 and IL-15 signaling is reduced but not absent in the presence of sγc [ 13 , 14 , 16 ]. Moreover, we propose that the modification of sγc to a multimer, which may improve affinity to γc cytokine receptors, would induce a more significant antitumor effect.…”
Section: Resultssupporting
confidence: 90%
“…In previous reports, we demonstrated that sγc regulates γc cytokine signaling with the generation of sγc-overexpressing transgenic (sγcTg) mice [ 13 , 14 , 16 ]. We found with in vitro and in vivo analysis of γc cytokine responsiveness that an elevated level of sγc dramatically dampens IL-2, IL-7, and IL-15 signaling.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, we observed that BT is not elevated in animals exercising even in BT water, indicating that the aquatic exercise is not strong enough to bring about changes in BT. The serum level of sγc, which is known to inhibit anti-tumor immune responses (19), decreases during tumor growth as part of its defense mechanism. The kinetics of sγc expression demonstrated are relatively late decline in housing mice compared with the exercise group (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…sγc interferes with IL-2 and IL-15 signaling in CD8 + T cells (6, 35, 36). Thus, we assessed the effect of siAp8 on IL-2 or IL-15 signaling in CD8 + T cells with anti-apoptotic Bcl-2 expression (Figures 4A,B).…”
Section: Resultsmentioning
confidence: 99%